Muli bamboo (Melocanna baccifera) as a new source of microcrystalline cellulose - Lalduhsanga Pachuau, David C. Vanlalfakawma, Shri Kant Tripathi, H. Lalhlenmawia (Journal of Applied Pharmaceutical Science, 2014)
Microcrystalline cellulose (MCC) was prepared by hydrochloric acid hydrolysis from Muli bamboo (Melocanna baccifera) fibers to tap its potential as a green source of MCC. The cellulose and α-cellulose yield from the original material were 62.5 and 54.8 % respectively. The physicochemical properties of the prepared MCC were investigated using Avicel PH101 as a comparator. Micromeritic properties of the powder MCC samples were analyzed by determining its average particle size, flow properties, particle porosity and density. The total ash and moisture content along with the swelling index were also determined. The prepared MCC was also characterized by fourier transformed infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and x-ray diffraction spectroscopy (XRD). Results from these analyses indicate that the Muli bamboo can be used as a green source of MCC.
Keywords: Microcrystalline cellulose, Melocanna baccifera, physicochemical properties.